Hubungan Kinerja Keuangan (Car, Npl, Nim Dan Bopo) dengan Harga Saham Bank Digital di BEI Selama Pandemi dan Pemulihan Ekonomi (2020–2023) - Burhan, Aditya (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Growth of digital banks in Indonesia. This study analyzes the relationship between financial indicators—Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Net Interest Margin (NIM), and Operating Expenses to Operating Income (BOPO)—and the stock prices of digital banks listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The research employs multiple linear regression analysis with secondary data from 7 digital banks, evaluated through classical assumption tests and hypothesis testing. The results indicate that CAR has a significant effect on stock prices (p < 0.05), while NPL, NIM, and BOPO do not have a significant influence. The regression model demonstrates that the independent variables contribute 57.9% to variations in stock prices. These findings highlight the importance of maintaining an optimal CAR to enhance investment appeal and financial stability for digital banks. The study also recommends exploring other external factors, such as market sentiment or government regulations, to better understand the dynamics of stock prices.